(untitled) (International Congress on Economics, Management and Business Studies, 2026)
The development of Islamic finance has become an important trend in the global financial system due to its ethical principles, risk-sharing mechanisms, and contribution to sustainable economic growth. This study examines the prospects and challenges of developing Islamic finance in Uzbekistan.